Perubahan Sosial dalam Perspektif Al-Qur’an: Studi Kepustakaan Tafsir Al-Azhar dan Tafsir Al-Misbah - Furqan MD, Muhammad; Mahmud, Hamidullah (Sahabat Publikasi, 2024)
In Islamic teachings, a human being lives according to religious norms. Real social change really covers all aspects of social life, thereby requiring a very long process to create a civilized social order in accordance with the guidance of the Al-Qur'an. To be able to do this, humans must mingle, or humans must interact which ultimately takes the form of integration. In a theoretical context, sociology places a transformation in the social environment as an event that occurs around society that is universal. The above studies in the current context are often explained using the term multiculturalism. In the Al-Qur'an, Al-Hujurat verse 13 states that the description of the purpose of creating humans by Allah for the same purpose is not necessarily in a narrow sense. M. Quraish Shihab tried to provide a way out, although in the end he still tended towards rational theology. Meanwhile, Hamka gave answers through preaching without any coercion through Al-Azhar interpretations.